(untitled) (Pesquisa Odontológica Brasileira, 2001)
This research aims to determine the relationship between the prevalence of caries and clinical and immunological classification in HIV-infected children. Ninety-two outpatients (42 male and 50 female subjects) with definitive diagnosis of HIV infection took part in this research. The patients were examined in order to determine the prevalence of caries (dmf and DMFT indexes), and medical data were collected from their medical records. The mean age of the subjects was 5.77 years. Although no statistical differences were found, young patients (up to 5 years old) had more caries when they were more clinically and immunologically compromised. The same fact was observed regarding older children.